Associação entre bruxismo e falhas mecânicas e biológicas na implantodontia : revisão sistemática e metanálise - Bertuzzi, Daniel (2020)
Introduction: The role of bruxism as an etiological factor in the biological failures and/or mechanical failures of implants have been studied in the literature with controversial results, and more studies need to be done. Objectives: This study had the objective to evaluate the relationship between bruxism with mechanical failure and/or biological failures in dentistry. Methods: A sistematic review was carried out in the PubMed/MEDLINE, Embase, Lilacs, Web Of Science, Scielo, Cinahl e Cochrane Central database. Adicionally, a manual search in the Gray literature was also carried out. The studies were analytical observational case-control and cohort studies, with three independent reviewers. The qualitative analysis was carried out using the Ottawa-Newcastle Scale - NOS. The star-system of the NOS was used as the study quality analysis. Results: The search retrieved 804 articles. The duplicates were excluded and, according to the eligibility criteria, 93 articles were selected for complete text reading. Among thtese, 30 were included for the final reading and 10 were included in the meta-analysis from the gray literature. In total, 40 articles were included for systematic review. The results showed a positive relationship between bruxism and biological and/or mechanical failure in implantes, despite the poor quality of the studies included. Limitations: Absent data, little description of the samples, absence of data for controls only for cases, heterogeneity of the types of implants used and types of cases used in the different types of studies. Conclusions: The results indicated na positive relationhip between bruxism and biological and/or mechanical failure of implants.